Integrating SERVQUAL and ECM to Explain E-Wallet Satisfaction and Continuance in Semi-Urban and Rural Indonesia - Juli Muslim Ihsan; Khairul Imtihan; Muhammad Fauzi Zulkarnaen (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study aims to analyze user satisfaction and continuance intention toward mobile payment applications in semi-urban and rural Indonesia by integrating the SERVQUAL framework and the Expectation–Confirmation Model (ECM). Although e-wallet adoption has increased rapidly, empirical evidence on post-adoption behavior in non-urban contexts remains limited. This study addresses this gap by examining how service quality, expectation, confirmation, and digital literacy shape satisfaction and continued usage. Using a quantitative survey, data were collected from 212 active DANA users in Central Lombok Regency during December 2025–January 2026 and analyzed using PLS-SEM with SmartPLS. The results show that among the five SERVQUAL dimensions, only empathy has a significant positive effect on user satisfaction. Expectation and confirmation significantly influence satisfaction, whereas perceived usefulness does not directly affect either satisfaction or continuance intention. User satisfaction and digital literacy significantly predict continuance intention, while the moderating effect of digital literacy is not supported. From a practical perspective, these findings indicate that providers should prioritize user assistance, communication, and expectation management rather than interface or technical attributes when serving semi-urban and rural markets. This study demonstrates that expectation fulfillment and relational-based service quality are more decisive for sustaining e-wallet usage than technical features in non-urban settings.